2005
DOI: 10.1007/bf02972977
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial constituents from fruits ofAilanthus altissima SWINGLE

Abstract: A new naturally occurring sterol, compound 5, and six known stigmasterols were isolated from fruits of Ailanthus altissima Swingle by repeated column chromatography and RP-HPLC. Their structures were identified as, 5alpha-stigmastane-3,6-dione (1), 3beta-hydroxystigmast-5-en-7-one (2), stigmast-5-ene-3beta, 7alpha-diol (3), 6alpha-hydroxystigmast-4-en-3-one (4), 5alpha-stigmastane-3beta, 6beta-diol (5), stigmast-4-ene-3beta, 6alpha-diol (6), stigmast-5-ene-3beta, 7alpha, 20xi-triol (7) by spectral analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 5 publications
2
28
0
1
Order By: Relevance
“…revealed the presence of only 3 phenolic acids. They were: gallic acid [30], caffeic [18] and ellagic [21]. Our study confirmed the presence of the three acids in the examined raw material and allowed for the identification of other acids found in the plant Ailanthus altissima Desf.…”
Section: Resultssupporting
confidence: 74%
“…revealed the presence of only 3 phenolic acids. They were: gallic acid [30], caffeic [18] and ellagic [21]. Our study confirmed the presence of the three acids in the examined raw material and allowed for the identification of other acids found in the plant Ailanthus altissima Desf.…”
Section: Resultssupporting
confidence: 74%
“…They are tri-terpenes with a wide spectrum of biological activities in animals and humans, including anti-inflammatory,[45] anti-bacterial,[46] antioxidative[47] and anti-cancerous. [48] Different groups of phytosterols include sitosterol, campesterol, stigmasterol, Δ 5 -avenasterol, sitostanol and campestanol.…”
Section: Diversity In Improved Varieties and Wild Speciesmentioning
confidence: 99%
“…Furthermore, they are also regarded as a kind of natural product with anti-inflammatory (Bouic, 2002), anti-bacterial (Zhao, Shao, Li, Xu, & Zhang, 2005), anti-oxidation (Hidalgo, Mercedes León, & Zamora, 2009;Van Rensburg, Daniels, Van Zyl, & Taljaard, 2000) and anti-cancer properties (Awad, Downie, Fink, & Kim, 2000;Gregg, 2001). Due to these beneficial health effects, it is important to obtain reliable methods to analyze sterols in different sterol-rich foods.…”
Section: Introductionmentioning
confidence: 99%